(untitled) (Nepal Agriculture Research Journal, 2010)
Yield loss in soybean due to leaf roller (Apoderus cyaneus Hope) was studied at Khumaltar during 1985 and 1986 seasons. Field experiments were conducted during vegetative as well as reproductive stages of soybean. Rolled leaves of soybean with eggs, grubs and pupae were collected from the field and reared in the laboratory for adults. Adults were introduced into nylon cages installed at the central rows of each plot just after germination of soybean. Insects were maintained at population density of 25, 50 and 100 per m2 density, the potential grain yield loss of cultivar, Ransom soybean in its vegetative and reproductive stages were 103 and 48 mg per day respectively from each adult of A. cyaneus. Percentages of yield losses were 36.2, 45.2, and 58.0 during vegetative and 37.5, 48.5 and 66.0 during reproductive stages from the insect population of 25, 50 and 100, respectively which, was not in accordance with the level of two and four fold increased population density of insect. Yield reduction was higher (260 and 108 mg per day) from each adult beetle at lower population level (25) in both vegetative and reproductive stages of soybean. Key words: Economic threshold level; leaf roller; physiological growth stages; yield loss DOI: 10.3126/narj.v6i0.3367 Nepal Agriculture Research Journal Vol.6 2005 pp.73-77